MOISTURE DETECTION FOR GROWING MEDIUM USING ARDUINO UNO - Sintianingrum, Ayu; Zuhelmi, Tomy Pratama; Aryanto, Iqbal May (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
The moisture content of soil or growing medium is one of crucial factor that significantly affects plant growth and achieving optimal harvest results. Therefore, detecting soil/growing medium moisture is essential to prevent plants from drying out due to insufficient water or being damaged by excessive watering. This study utilized an Arduino Uno to measure the moisture of the growing medium. Based on from the results and discussions, the device designed in this study has been able to detect changes in the moisture levels of the growing medium after watering and can serve as an alert if the growing medium becomes too dry, as indicated by the LED installed on the device.